Fire Retardancy Behavior of Polymer/Clay Nanocomposites - Zope, Indraneel Suhas; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This thesis investigates the early ignition behavior of polymer/clay nanocomposites, which are perceived as potential eco-friendly flame retardant systems. It examines the correlation between clay structural chemistry and high-temperature transformations with clay-assisted decomposition of organic macromolecules. In particular, it investigates the unique effects of metal ions like Mg2+, Al3+ and Fe3+ that are inherent in clays (smectite) on the combustion and thermo-oxidative decomposition of polyamide 6. The results indicate that metal ions present on/in montmorillonite platelets have preferential reactivity towards peroxy/alkoxy groups during polyamide 6 thermal decomposition.  Lastly, a simple solution in the form of a physical coating on clay surface is proposed, based on the role of polymer-clay interfacial interaction.
Introduction -- Literature Review -- Experimental Methodology -- Decomposition Behavior of Metal-ion Exchanged Clay -- Thermo-oxidative Decomposition Behavior of Polyamide 6 Nanocomposites with Metal-ion Exchanged Clays -- Thermo-oxidative Decomposition Behavior of Polyamide 6 Nanocomposites with Structurally Different Clays -- Controlling the Interfacial Interactions Between Clay and Host Polyamide 6 Matrix -- Clay Catalysis and Fire Retardancy of Polymer/Clay Nanocomposites: A Complete Overview.
Keywords: Ceramic materials; Materials; Polymers; Ceramics; Materials Engineering; Polymers